A Comprehensive Analysis of Armenia's Innovation Input and Output - Tadevosyan, Ruzanna («Տնտեսագետ» հրատ․)
The article explores the intricate landscape of Armenia's innovation ecosystem, thoroughly examining its strengths and weaknesses. The study using the Global Innovation Index (GII) as a benchmark reveals a complex narrative. While Armenia exhibits impressive performance in innovation output, securing the 62nd position globally in 2023, challenges prevail in innovation input, where Armenia ranks 83rd. The article emphasizes the imperative for targeted policies addressing institutional, educational, scientific, and economic dimensions. It advocates for a systematic approach, positioning the Department of Innovative, Knowledge-Based Economy of the Ministry of Economy of the RA as a crucial actor, collaborating with diverse spheres of policymakers to optimize Armenia's innovative potential. Amid global dynamics, the article delves into external and internal influences, presenting a roadmap for improvements. The article could serve as a guide for policymakers interested in leading Armenia to a more innovative route.
Keywords: Education; Innovation